Development of Literature Model Based on Multiplatform Application - Hidayat, Muhammad Taufik; Junaidi, Teuku; Rizki, Azrul; Sukirno, Sukirno; Nuriana, Nuriana (Journal of Nonformal Education, 2022)
This research was conducted based on the condition of the low grades of students in the field of literacy at PKBM Huda Wan Nur. This is due to the lack of application of updated and digital platform-based learning media used by teachers in the teaching process, especially reading and writing literacy and writing local wisdom texts. This research is in the form of a qualitative descriptive which aims to improve student literacy, especially literacy with multiplatform media concepts that combine online and offline learning effectively at PKBM Huda Wan Nur, Langsa City. The subjects of this study were students and teachers of PKBM Huda Wan Nur Langsa City. The research was conducted by applying the Research Development method or the RD method. The data were analyzed by describing the questionnaire containing the Likert scale and the percentage of the product feasibility test. The results show that during the implementation of learning using multiplatform media, students' work at school is at a good level compared to before. Then, the results of students' ability to use multi-platform applications are at a good level for LMS, Google Meet, and Google Classroom, while for Youtube, zoom meetings, and Instagram are at a very good level. For this reason, it can be said that the development of reading and writing literacy with multi-flatform applications has succeeded in improving students' writing skills, especially local wisdom texts. This research is a new thing that was carried out at PKBM Huda Wan Nur and Langsa City by combining a literacy system with multi-platform digital media that is beneficial for the development of knowledge, especially writing texts for students. In addition, it is also useful for teachers to take the first step in developing students' literacy skills by using digital media.